McQueen [videorecording (DVD)] (Vertical Entertainment, 2018)
A personal look at the extraordinary life, career, and artistry of Alexander McQueen. Through exclusive interviews with his closest friends and family, recovered archives, exquisite visuals and music, it is an authentic celebration and thrilling portrait of an inspired yet tortured fashion visionary.